Socio-Economic Analysis from the Perspective of Waste Management and the Environment through Community Empowerment Mediation in Belawan, Medan - Nalom Siagian; Natalia ET Sihombing; Nova Anastasia Turnip; Rut Onike Lubis; Suci Sang Primadona Gulo (Jurnal Mamangan, 2024)
The river and beach coasts in the Belawan area that are currently faced with waste problems not only cause environmental and health pollution, but also serious problems that have an impact on the regional economy. Pollution due to waste in the sea will indirectly threaten many things on earth. Including, threats to humans. As a result of indirect threats from waste in the sea, humans will feel the impact on the environment. Poor waste management also has an impact on the environment, causing the aesthetics of the environment to be less pleasing to the eye, for example, the large amount of scattered waste that disrupts the freshness of the air in the community environment. Regulators and operators as implementers of regulations must make good efforts so that waste management in the coastal areas of rivers and beaches in Belawan is carried out through community empowerment. Good waste management planning will provide socio-economic value to the community if followed by community empowerment. The formulation of the problem in this study is: how much direct influence does waste management planning have on the environment; the direct influence of waste management planning on empowerment; the direct influence of empowerment on the environment and the indirect influence of waste management planning on the environment through empowerment. The purpose of this study is to analyze the extent of the direct influence of waste management planning on the environment; direct influence of waste management planning on empowerment; direct influence of empowerment on the environment and indirect influence of waste management planning on the environment through empowerment. This study is a causal associative study with a quantitative approach. The data analysis technique used is descriptive and confirmatory factor analysis, structural model analysis with hypothesis testing is carried out using the t-Value value with a significance level of 0.05.